2005
DOI: 10.1002/pi.1890
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and properties evaluation of copolymers of 2,3,4,5,6‐pentafluorostyrene and N‐phenylmaleimide

Abstract: Copolymers of 2,3,4,5,6‐pentafluorostyrene (PFS) having a combination of high hydrophobicity and high glass transition temperature (Tg) are reported here for the first time. The copolymerization was carried out using N‐phenylmaleimide (NPM) as the comonomer and azobisisobutyronitrile (AIBN) as the initiator under both conventional thermal heating and microwave heating. The initial copolymerization rate was found to be higher under microwave heating than under thermal heating. The copolymerization parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
14
2
Order By: Relevance
“…The review article by Schubert et al [1] shows the rapid progress in the field of microwave-assisted polymer syntheses including step-growth polymerizations, ring-opening polymerizations and radical polymerizations. Although there is a large number of literature available on microwave-assisted conventional free radical polymerizations, [2][3][4][5][6] the use of microwaves in the field of controlled radical polymerizations is not that much exploited but gaining pace slowly. Zhu et al [7] investigated the atom transfer radical polymerization (ATRP) of styrene under pulsed microwave irradiation and showed an increase in the rate without affecting the controlled characteristic of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The review article by Schubert et al [1] shows the rapid progress in the field of microwave-assisted polymer syntheses including step-growth polymerizations, ring-opening polymerizations and radical polymerizations. Although there is a large number of literature available on microwave-assisted conventional free radical polymerizations, [2][3][4][5][6] the use of microwaves in the field of controlled radical polymerizations is not that much exploited but gaining pace slowly. Zhu et al [7] investigated the atom transfer radical polymerization (ATRP) of styrene under pulsed microwave irradiation and showed an increase in the rate without affecting the controlled characteristic of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Pitois et al studied the copolymerization of PFS with glycidyl methacrylate (GMA) and measured reactivity ratios r PFS = 0.38 and r GMA = 0.89, which is fairly typical of styrenics with methacrylates. PFS was also copolymerized with n ‐phenyl maleimide (PMI) with r PFS = 0.28 and r PMI = 0.86 . Thus, there is no data from PFS copolymerizations to suggest that the chain end would be terminated with a less stable methacrylate group.…”
Section: Resultsmentioning
confidence: 99%
“…[31] It was found that the initial copolymerization rate was higher in the case of microwaveassisted heating, but a lower maximum conversion was obtained on the other hand. Recently, Galli and coworkers synthesized a new hydantoin monomer for subsequent copolymerization with acrylates.…”
Section: Free-radical Polymerizationsmentioning
confidence: 97%